ANALISIS CITRA MEREK TERHADAP MINAT KONSUMEN PRODUK THE BODY SHOP PALANGKA RAYA - Noorjaya Nahan; Vivy Kristinae (Universitas Tidar, 2019)
Competition for environmentally friendly products in the current era is increasing, resulting in consumer interest in products that require information about products. The purpose of this study is to identify the extent of brand image in the community towards environmentally friendly products in The Body Shop products in Palangka Raya which are environmentally friendly products and can be used from teens to parents. Research with a sample of 100 consumers with consumer age control variables and analyzed quantitatively with SPSS 24.0 resulted in a significant brand image that could increase consumer interest and significant mediation promotion in making repeat purchases. Research implications for increasing consumer interest in products by maintaining product image and relentless promotion as a business strategy so that they are able to compete in environmentally friendly products.